ANALYSIS OF EXISTING MODELS OF PRODUCTION PROCESS CONTROLLING IN MANUFACTURING AND SERVICE INDUSTRIES - Vladimir Y. Ivanov (Advanced Engineering Research, 2012)
The definition of controlling is given. The factors influencing the controlling system at the enterprise are considered. The comparative analysis of American and German models is made. The conclusion on their availability at the Russian enterprises is drawn.